Understanding as Usability and Context-Sensitivity to Interests. - Søndergaard, Andreas (Philosophia, 2023)
Is understanding subject to a factivity constraint? That is, must the agent's representation of some subject matter be accurate in order for her to understand that subject matter? 'No', I argue in this paper. As an alternative, I formulate a novel manipulationist account of understanding. Rather than correctly representing, understanding, on this account, is a matter of being able to manipulate a representation of the world to satisfy contextually salient interests. This account of understanding is preferable to factivism, I argue, mainly for simplicity reasons. While it explains the intuitive data about understanding as successfully as factivist accounts, it is simpler by virtue of reducing the value truth bestows on understanding to that of usability.